(3GdJgPjHs - (3GdMSjf Hf eSYhO Hf eMeO, GdaqQGA, Ch GHf GdnanqQGA, CHh eMeO, hjdbH HeMjj GdSqfI, GdHZhj,J (B510 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf CTQa GdCehQ bOQkG hCYXegG CLQkG JYde GdYde s
(3BNQgG (B:s
(3Je GdLRA GdChd ef cJGH GdJgPjH hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg CLeYjf s
(3GdfSNI HgG MhGTs
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B259 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B61s
Keywords: (3Gdabg GdTGaYjs